Ionic Surface Dielectric Properties Distribution on Reservoir Sandstone - Sikiru, Surajudeen; Afolabi, Lukmon Owolabi; Borhana Omran, Abdoulhdi Amhmad; M Elfaghi, Abdulhafid (International Journal of Integrated Engineering, 2021)
The petrophysical and dielectric properties for both carbonate and saturated sandstone with monovalent and divalent electrolyte they are accurately modeling of anisotropic dielectric properties has been the major research area in oil and gas industries for effective sweep efficiency. The reservoir petrophysical properties consist of cation and anion exchange capacity on a specific area and the sandstone porosity. The transportation of the ions is a charge carrier that mediates conduction in the pore fluids under the electrical double layers that exist between the minerals and the pore fluids interface. The dielectric anisotropic and the frequency-dependent behavior of reservoir sandstone with the minerals will be fully elucidated, it was revealed from the result obtained the effect of the anisotropic dielectric properties on the reservoir sandstone based on the influx of NaCl electrolyte modify the wettability of rock formation from oil-wet to water-wet at 9000 and 11000 ppm concentration with the aids of the electromagnetic field. The resistivity index of the reservoir sandstone reduces with the increase of electrolyte to the system.